Wheat F-Box Protein Gene TaFBA1 Is Involved in Plant Tolerance to Heat Stress - Li, Qinxue; Wang, Wenqiang; Wang, Wenlong; Zhang, Guangqiang; Liu, Yang; Wang, Yong; Wang, Wei (Frontiers in Plant Science, 2018)
Adverse environmental conditions, including high temperature, often affect the growth and production of crops worldwide. F-box protein, a core component of the Skp1-Cullin-F-box (SCF) E3 ligase complex, plays an important role in abiotic stress responses. A previously cloned gene from wheat, TaFBA1, encodes a homologous F-box protein. A Yeast two-Hybrid (Y2H) assay showed that TaFBA1 interacted with other SCF proteins. We found that the expression of TaFBA1 was induced by heat stress (45°C). Overexpression of TaFBA1 enhanced heat stress tolerance in transgenic tobacco, because growth inhibition was reduced and photosynthesis increased compared to the wild type (WT) plants. Furthermore, the accumulation of H2O2, O2-, and carbonyl protein decreased and cell damage was alleviated in transgenic plants under heat stress, which resulted in less oxidative damage. However, the transgenic plants contained more enzymatic antioxidants after heat stress, which might be related to the regulation of some antioxidant gene expressions. The qRT-PCR analysis showed that overexpression of TaFBA1 upregulated the expression of genes involved in reactive oxygen species scavenging, proline biosynthesis, and abiotic stress responses. The results suggested that TaFBA1 may improve enzymatic antioxidant levels and regulate gene expression by interacting with other proteins, which leads to the enhanced heat stress tolerance seen in the transgenic plants.